A reactivation project of a district of the historical centre of Genova. Issue 1 (October 2021) - Vite, Clara; Morbiducci, Renata; Morini, Andrea
Abstract: Many of the recovery and renovation interventions of the existing heritage conducted today in Europe are the result of urban policies careful to reduce land consumption and improve safety, comfort, and quality according to the needs of users. A substantial historical building heritage characterizes the Italian territory. Historical centres' regeneration is one of the constant and recurring themes of extreme complexity and importance due to the extension, the peculiarities, and the conformation in some cities. The contribution presented deals with the redevelopment and reactivation of a historic district of Genoa, which has one of the largest historical centres in Europe. Innovation, together with the three pillars of sustainability (environmental, social, and economic), are the engines of this pilot project to trigger virtuous processes for the district's reactivation. It is an area of the historic centre with high potential in its proximity to essential activities of the city, the port, and infrastructure. The proposed plan for the regeneration of the area resulted from an in-depth analysis of the territory's state and existing practices and was carried out in close collaboration with the reference bodies and actors involved. This preliminary analysis made it possible to identify the strengths and weaknesses that were the starting point for the pilot project. The article then focuses on two specific aspects. Some of the university's buildings are in the district, and this is the starting strength for creating a "diffuse" university campus with areas to serve students. On the other hand, the open spaces are the point of weakness on which we have worked with outdoor lighting to increase the degree of security of the neighbourhood and enhance the peculiarities and value of existing spaces.